1985
DOI: 10.1042/bj2270079
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of inositol trisphosphate formation in hepatocytes by vasopressin, adrenaline and angiotensin II and its relationship to changes in cytosolic free Ca2+

Abstract: At maximally effective concentrations, vasopressin (10(-7) M) increased myo-inositol trisphosphate (IP3) in isolated rat hepatocytes by 100% at 3 s and 150% at 6 s, while adrenaline (epinephrine) (10(-5) M) produced a 17% increase at 3 s and a 30% increase at 6 s. These increases were maintained for at least 10 min. Both agents increased cytosolic free Ca2+ [( Ca2+]i) maximally by 5 s. Increases in IP3 were also observed with angiotensin II and ATP, but not with glucagon or platelet-activating factor. The dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(39 citation statements)
references
References 43 publications
(28 reference statements)
4
35
0
Order By: Relevance
“…The interesting observation of Assimacoupoulus-Jeanett et al (1982) and Morgan et al (1983) that increases in dibutyryl cyclic AMP are able to reverse vasopressin-induced Ca2+ mobilization (see also Crane et al, 1982) appears to be consistent with the finding (Keppens and De Wulf, 1984) that vasopressin inhibits the maintenance of cyclic AMP levels in hepatocytes by activating phosphodiesterase. Charest et al (1985b) have shown that glucagon is able to potentiate Ca2+ inflow induced by extracellular ATP.…”
Section: Effects Of Glucagon or Of Dibutyryl Cyclic Amp On Ca2+ Fluxementioning
confidence: 99%
See 1 more Smart Citation
“…The interesting observation of Assimacoupoulus-Jeanett et al (1982) and Morgan et al (1983) that increases in dibutyryl cyclic AMP are able to reverse vasopressin-induced Ca2+ mobilization (see also Crane et al, 1982) appears to be consistent with the finding (Keppens and De Wulf, 1984) that vasopressin inhibits the maintenance of cyclic AMP levels in hepatocytes by activating phosphodiesterase. Charest et al (1985b) have shown that glucagon is able to potentiate Ca2+ inflow induced by extracellular ATP.…”
Section: Effects Of Glucagon or Of Dibutyryl Cyclic Amp On Ca2+ Fluxementioning
confidence: 99%
“…Earlier studies from a number of laboratories indicated that glucagon alone has no significant effect on Ins(1,4,5)P3 generation in hepatocytes (Prpic et al, 1982;Kaibuchi et al, 1982;Charest et al, 1985b) and fails to increase Ins(1,4,5)P3 breakdown (Creba and Hansen (1987) showed that glucagon, while enhancing adrenaline-induced Ca2+ inflow in hepatocytes, had no effect on the generation of Ins(1,4,5)P3. Burgess et al (1986Burgess et al ( , 1991 found (like Cocks et al, 1984) that isoprenaline administration to guinea pig hepatocytes caused little, if any, increase in Ins(1,4,5)P3 formation in the absence or presence of angiotensin II.…”
Section: Possible Loci In the Signalling Transduction Pathways Where mentioning
confidence: 99%
“…angiotensinogen secretion The major signal transduction pathway by which angiotensin II influences intracellular functions in hepatocytes seems to be the activation of phospholipase C, release of both inositol trisphosphate and diacylglycerol, and the subsequent increase in intracellular calcium and activation of the Ca'+-activated, phospholipid-dependent protein kinase (protein kinase C), respectively [12,13]. In addition, angiotensin II has been shown to inhibit adenylate cyclase and reduce intracellular CAMP [14,15].…”
Section: Modulation Of Second Messengers Andmentioning
confidence: 99%
“…Hence, a submaximal increase (35%) in cAMP formation already yielded a maximal activation of glycogen phosphorylase. This lack of a strict correlation of cAMP formation and activation of glycogen phosphorylase, where cAMP apparently is produced in excess, is a well-known phenomenon [57, 581 which is also observed with the second messenger InsP, [59].…”
Section: Involvement Of Different Signal Chainsmentioning
confidence: 99%